Association of Tumor Necrosis Factor Inhibitor Treatment With Reduced Indices of Subclinical Atherosclerosis in Patients With Psoriatic Disease. Issue 3 (6th February 2018) - Eder, Lihi; Joshi, Aditya A.; Dey, Amit K.; Cook, Richard; Siegel, Evan L.; Gladman, Dafna D.; Mehta, Nehal N.
Abstract : Objective: To assess the effect of tumor necrosis factor inhibitors (TNFi) on subclinical cardiovascular disease in patients with psoriatic disease. Methods: We performed a 2‐stage study. In stage 1, carotid total plaque area was assessed in patients with psoriasis or psoriatic arthritis (PsA) (n = 319) by ultrasound at baseline and after 2–3 years. The annual progression rate of atherosclerosis was the outcome of interest. In stage 2, PsA patients receiving TNFi (n = 21) and age‐ and sex‐matched PsA patients not receiving any biologic agent (n = 13) underwent 18 F‐fluorodeoxyglucose–positron emission tomography/computed tomography at baseline and 1 year to assess vascular inflammation, measured as target‐to‐background ratio (TBR). In both stages, multivariable regression analyses adjusted for cardiovascular risk factors and use of statins were performed. Results: In stage 1, men had significantly higher atherosclerosis progression than women ( P < 0.001). TNFi was associated with reduced atherosclerosis progression in men after controlling for cardiovascular risk and use of statins (adjusted β = −2.20 [95% confidence interval −3.41, −1.00], P < 0.001). There was no association between TNFi and atherosclerosis progression in women ( P = 0.74). In stage 2, patients receiving TNFi had reduced TBR at 1 year ( P = 0.03). Those not receiving TNFi had no significant change in TBR ( P = 0.32). The improvement in aortic vascular inflammation in the TNFi group was independent of cardiovascular risk factors (adjusted β = −0.41 [95% confidence interval −0.74, −0.08], P = 0.02). Conclusion: Our findings indicate that TNFi treatment is associated with reduced progression of carotid plaques in men and improvement in vascular inflammation in both men and women with psoriatic disease.